2006
DOI: 10.3852/mycologia.98.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus ibericus: a new species of section Nigri isolated from grapes

Abstract: As part of a study on the ochratoxin producing mycoflora of grapes, several Aspergillus strains were isolated and tested for their ochratoxin A (OTA) producing abilities. Aspergillus strains of the section Nigri, which did not produce detectable amounts of OTA but which had a similar morphology to A. carbonarius, were isolated from wine grapes and/or dried vine fruit in Portugal and Spain. These strains, however, have characters that allow morphological distinction from the other species in the section, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 35 publications
4
29
1
2
Order By: Relevance
“…2), it is clear that this novel species has conspicuously spiny conidia when young and that verruculose conidia develop at maturity. The conidial ornamentation of A. sclerotiicarbonarius is more similar to that of the recently described species, A. ibericus (Serra et al, 2006) than to A. carbonarius.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…2), it is clear that this novel species has conspicuously spiny conidia when young and that verruculose conidia develop at maturity. The conidial ornamentation of A. sclerotiicarbonarius is more similar to that of the recently described species, A. ibericus (Serra et al, 2006) than to A. carbonarius.…”
Section: Resultssupporting
confidence: 73%
“…Even though many black species of the genus Aspergillus have been described (Mosseray, 1934;Raper & Fennell, 1965;Al-Musallam, 1979, Kozakiewicz, 1989Abarca et al, 2004), and many of these taxa have been reduced to synonymy, eight novel species have been described recently: Aspergillus costaricaensis, Aspergillus lacticoffeatus, Aspergillus piperis and Aspergillus sclerotioniger (Samson et al, 2004b), Aspergillus vadensis (de Vries et al, 2005), Aspergillus ibericus (Serra et al, 2006), Aspergillus brasiliensis (Varga et al, 2007) and Aspergillus uvarum (Samson et al, 2007;Perrone et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For example, regarding the variability of the ITS region, six parsimony informative sites were present, while some Aspergillus species cannot even be distinguished using ITS sequence data alone (41,55). The two clades identified in P. variotii based on ITS sequence data are less related to each other than, e.g., A. niger to A. tubingensis (41) or A. ibericus to A. carbonarius (43). However, mating experiments revealed that these clades represent a single biological species.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and characterization of new fungal species are often encountered in literature. Within the black Aspergilli, to which several efficient beta-glucosidase products belong, several new species have been identified within recent years [94,95,96,97,98,99,100,101,102]. Screening for new enzymes can be performed at the genomic as well as the proteomic level—in either case, it can be a mixed gene or protein pool or a sample representing a specific species.…”
Section: New and Improved Beta-glucosidasesmentioning
confidence: 99%